It's Not Only What You Say, But How You Say It: Investigating the Potential of Prosodic Analysis as a Method to Study Teacher's Talk - Raija Hämäläinen; Bram De Wever; Teija Waaramaa; Anne-Maria Laukkanen; Joni Lämsä (EARLI, 2018)
In this study, we introduce new insights into prosodic analyses as an emerging method to study teacher talk. We claim that the prosodic aspects (features of speech such as intonation, volume, and pace) of talk are important, but under-represented in the learning sciences. These prosodic aspects may be used to complement, intensify or even reverse the linguistic content of speech. Thus far, most research on classrooms has focused on the content (what is said) rather than on understanding the meaning of the prosodic features (how it is said) of talk. In this study, we introduce prosodic analyses as a method to study classroom discussions. Our exploratory experiment focuses on the prosodic perspective of teacher's talk to shed light on the features of classroom talk. We present a case in which we align prosodic features with the content of teacher's talk during a nine-week physics course. This article shows that prosodic analyses may have added value for research on learning and professional development. Namely, we illustrate that acting in an authentic classroom setting might trigger specific prosodic aspects in teacher's talk. We further found indications that the teacher applied different voice prosody regarding certain patterns of classroom talk. For the future, we suggest that a combination of content and prosodic analysis is a promising tool for gaining new insights into classroom talk.